Quality Assurance in Africa: Towards a Continental Higher Education and Research Space - Shabani, Juma; Okebukola, Peter; Oyewole, Olusola (International Journal of African Higher Education, 2014)
This article is a critical review of quality assurance in higher education in Africa with the purpose of identifying recent results, challenges still to be faced, and actions required to forcefully move towards the construction of an African higher education and research space (AHERS). The article identifies factors responsible for the decline in quality and proposes an integrated and holistic conceptual framework for analysing quality assurance. It reviews the various initiatives implemented in recent years and identifies, among the results, the establishment of new quality assurance agencies, the creation of a regional quality assurance system in East Africa, the strengthening of institutional development capacities, and capacity building in competencies-based curriculum reform. Challenges include the limited human capacity of quality assurance agencies, ineffectiveness in implementing harmonisation strategies, and the lack of tools required to compare qualifications. The article concludes with recommendations on promoting student and staff mobility to help realise the creation of AHERS. Cet article est une critique de l’assurance qualité de l’enseignement supérieur en Afrique. Il a pour objectif d’identifier les récentes études, les défis à relever, et les actions nécessaires pour provoquer la création d’un Espace Africain pour l’Enseignement Supérieur et la Recherche (AHERS). Cet article identifie les facteurs à l’origine du déclin de la qualité et propose un cadre théorique holistique complet pour analyser l’assurance qualité. Il critique les différentes initiatives mises en place ces dernières années et s’attarde plus spécifiquement sur la fondation de nouvelles agences chargées de l’assurance qualité, la création d’un système régional d’assurance qualité en Afrique de l’Est, le renforcement des capacités de développement des institutions, et le développement des capacités nécessaires pour établir une réforme des programmes axée sur les compétences. La capacité humaine limitée des agences d’assurance qualité, l’inefficacité quant à l’implémentation des stratégies d’harmonisation et le manque d’outils pour comparer les diplômes font partie des difficultés majeures. Nous terminons cet article en encourageant la mobilité des étudiants et des professeurs pour provoquer la création d’un Espace Africain pour l’Enseignement Supérieur et la Recherche.